Building Active Awareness About Waste Among Santri at Islamic Boarding School X in Malang (Lembaga Pengembangan Kinerja Dosen, 2026)
The global environmental crisis has had an impact on religious educational environments such as Islamic boarding schools. The phenomenon at Pondok Pesantren X Malang shows a gap between the normative knowledge of students about cleanliness and their actual behavior, such as the habit of littering. This study is based on the hypothesis that students' ecological awareness is formed through the interaction between knowledge, experience, and the social context in the pesantren. The research method uses an exploratory qualitative approach with a grounded research design through in-depth interviews, participatory observation, and documentation of six students aged 10–12 years. The results revealed three main themes: knowledge about trash (45%), irresponsible habits (34%), and active awareness (21%). These findings confirm that although santri have a fairly good initial understanding, behavioral change is still hindered by social habits. In conclusion, strengthening reflective education, the exemplary role of ustadz, and institutional support are crucial for building sustainable ecological awareness in Islamic boarding schools.